The monetary value of human life losses associated with COVID-19 in Africa: A human capital approach - Joses M. Kirigia; Germano M. Mwabu (Economies, 2025)
Background: By 30 June 2021, the 54 African sovereign nations had reported 5,465,790 laboratory-confirmed COVID-19 cases (including 142,171 deaths). This study aimed to estimate the monetary value of human life losses, indirect and direct costs, and the potential cost reductions due to vaccinations for advocacy use by Ministries of Health in Africa. Methods: We employed both the human capital approach to value human lives lost and an abridged total cost-of-illness methodology to estimate the indirect and direct costs of COVID-19 across 54 African countries. The secondary data analyzed was from different sources. Results: The 142,171 human lives lost had an estimated discounted total monetary value of Int6,684,101,196, i.e., Int47,015 per life loss and Int4.88 per person in the population. The estimated total cost of the actual reported 5,514,709 COVID-19 cases was Int7,155,473,174, which comprised a total direct cost of Int3,981,927,049 (55.6%) and an indirect cost of Int3,173,546,125 (44.4%). We projected that vaccination of all the eligible people in the population would potentially save the African continent approximately Int41,624,735,824. The average total saving per person is approximately Int30.4. Conclusions: The COVID-19 pandemic resulted in substantial monetary value of human life losses and indirect and direct costs.
Keywords: 330; COVID-19; Africa; direct cost; gross domestic product; human capital approach; indirect cost; value of life